2019
DOI: 10.1088/1361-6463/ab4697
|View full text |Cite
|
Sign up to set email alerts
|

Giant tunable Goos–Hänchen shifts based on surface plasmon resonance with Dirac semimetal films

Abstract: Surface plasmon resonance (SPR) with bulk Dirac semimetals (BDS) has been proposed to enhance the Goos-Hänchen (GH) shift. It is found that a large positive and negative GH shift can be obtained by adjusting the thickness of the BDS film, and the GH shift is very sensitive to the Fermi level of the BDS film. By changing the Fermi level of the BDS film, we can get a controllable negative GH shift. The largest GH shift of the proposed configuration, as large as 361.4 times the incident wavelength, has been obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…In the traditional Au (Ag) sensor, we used an excitation wavelength of 632.8 nm, Au (Ag) film thickness of 45 nm, and n Au = 0.7900 + 17.3109i, n Ag = 0.1675 + 3.4728i. The parameters are consistent with previous studies [ 21 , 52 , 53 ]. When the refractive index of the sensing medium changes 0.002, the GH shifts changed by 51.7 .According to Equation (12), the sensitivity can be obtained as S n .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the traditional Au (Ag) sensor, we used an excitation wavelength of 632.8 nm, Au (Ag) film thickness of 45 nm, and n Au = 0.7900 + 17.3109i, n Ag = 0.1675 + 3.4728i. The parameters are consistent with previous studies [ 21 , 52 , 53 ]. When the refractive index of the sensing medium changes 0.002, the GH shifts changed by 51.7 .According to Equation (12), the sensitivity can be obtained as S n .…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have shown that the conductivity of the DSM can be described by the Kubo formula [ 21 , 43 ]. For and long-wavelength limit, the optical conductivity can be written analytically as where g is the degeneracy factor, is the Fermi velocity, is the step function, and represents the high-energy cutoff of the linear model.…”
Section: Theoretical Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Since the optical properties of graphene can be tuned by changing its chemical potential or Fermi energy, several graphene-based optical systems have been theoretically, and numerically demonstrated the tuning of G-H shifts. [24][25][26][27][28][29][30][31][32] Moreover, tunable G-H shift has been theoretically and numerically investigated in several optical systems such as Dirac semimetal films by exciting the SPs, [33] a cavity with four-level quantum system, [34] a weakly absorbing epsilon-near-zero slab [27] and a nanocomposite structurally chiral medium. [35] In addition, the forward tuning of G-H shift in the visible wavelengths (with maximum and minimum values only) has been experimentally demonstrated using a PCM-based HMM by directly annealing the HMM at higher temperature [36,37] (280 °C).…”
Section: Doi: 101002/adma202006926mentioning
confidence: 99%
“…A high Q-factor resonance also leads to dramatic change in the reflection phase around the resonant peak 41 . Based on these, numerous theoretical and experimental works have been devoted to enhancing the GH shift on different structure interfaces such as weakly absorbing slab [42][43][44] , surface plasmon resonator [45][46][47][48] , Bloch surface wave resonator [49][50][51] , dielectric metagrating and photonic crystal slab 52,53 . However, there is a common defect in these two enhancement mechanisms: although the maximum GH shift can be enhanced to the length of orders of wavelength, it is exactly located at the reflection dip with extremely low reflectance, which is difficult to be detected.…”
Section: Introductionmentioning
confidence: 99%